The all-wavelength extended groth strip international survey (AEGIS) data sets - Davis, M; Guhathakurta, P; Konidaris, N; Newman, J; Ashby, M; Biggs, A; Barmby, P; Bundy, K; Chapman, S; Coil, A; Conselice, C; Cooper, M; et al. (Institute of Physics Publishing, 2007)
In this the first of a series of Letters, we present a panchromatic data set in the Extended Groth Strip region of the sky. Our survey, the All-Wavelength Extended Groth Strip International Survey (AEGIS), aims to study the physical properties and evolutionary processes of galaxies at z ∼ 1. It includes the following deep, wide-field imaging data sets: Chandra/ACIS X-ray, GALEX ultraviolet, CFHT/MegaCam Legacy Survey optical, CFHT/CFH12K optical, Hubble Space Telescope/ACS optical and NICMOS near-infrared, Palomar/WIRC near-infrared, Spitzer/IRAC mid-infrared, Spitzer/MIPS far-infrared, and VLA radio continuum. In addition, this region of the sky has been targeted for extensive spectroscopy using the Deep Imaging Multi-Object Spectrograph (DEIMOS) on the Keck II 10 m telescope. Our survey is compared to other large multiwavelength surveys in terms of depth and sky coverage. © 2007. The American Astronomical Sociey, All rights reserved.